Kontrasten 47|67 : schilderkunst in België. - Alechinsky, Pierre; Bekkers, Ludo; Bilcke, Maurits; Callewaert, Marc; Claus, Hugo, 1929-2008; Cruls, Tito; Delevoy, Robert L.; Geirlandt, Karel J.; Guiette, René; Langui, Emile; Legrand, Francine-Claire; Mara, Pol; et al. (Antwerpen : KMSKA (Koninklijk Museum voor Schone Kunsten Antwerpen) Antwerpen, 1968)
Alechinsky, Pierre ; Van Anderlecht, Englebert ; Bertrand, Gaston ; Bogart, Bram ; Bonnet, Anne ; Van Breedam, Camiel ; Burssens, Jan ; Cox, Jan ; D'Haese, Roel ; Delahaut, Jo ; Gentils, Vic ; Guiette, René ; Van Hoeydonck, Paul ; Landuyt, Octave ; de Leeuw, Bert ; Van Lint, Louis ; Mara, Pol ; Mendelson, Marc ; Mesens, E.L.T. ; Mortier, Antoine ; Peire, Luc ; Raveel, Roger ; Servranckx, Victor ; Van Severen, Dan ; Slabbinck, Rik ; Somville, Roger ; Vandenbranden, Guy ; Vandercam, Serge ; Verheyen, Jef ; Vlerick ; Wyckaert, Maurice
biog. & bibliog. [1 p.]
P. Vlerick p. 244
Schenking Pierre Vlerick
Nederlands
Exhibition. Kontrasten 47-67 : schilderkunst in België, KMSKA (Koninklijk Museum voor Schone Kunsten, Antwerpen, 18.02.1968 - 12.05.1968
kunstcatalogus
Keywords: België